Three-step switching frequency selection criteria for the generalized CLLC-type DC transformer in hybrid AC-DC microgrid - Huang, Jingjing (2022)
For hybrid ac-dc microgrids, the widely applied high-frequency dc transformer (DCT) is usually scheduled to operate at resonant frequency with 50% duty-cycle-based semiregulated control to ensure the power transmission (PT), improve its power-density, and simplify the system-level control. However, for a real DCT, it may exist more than one resonant frequency that exhibit totally different features, which may seriously degrade the PT ability if the inappropriate switching frequency is selected. Meanwhile, the actual values of the DCT inductances and capacitances are also changing with the power, temperature, etc., which may lead to the practical resonant frequency's variation. Thus, how to select the suitable switching frequency to guarantee the PT ability against the parameter variation becomes a challenge. In this paper, three-step switching frequency selection criteria (SFSC) are proposed. A generalized CLLC-type DCT (GCLLC-DCT) model is extracted to make the proposed approach available for the LLC-, CLL-, symmetric CLLC-, and asymmetric CLLC-type topologies. For convenience, the definition of the active power transmission ratio (APTR) is introduced to help evaluate the PT ability. First, the number, value, and impact variables of the resonant frequency are derived and analyzed in Step I as the preliminary. Afterward, the optimum resonant frequency is confirmed for the GCLLC-DCT as the criterion based on the APTR in Step II. At last, the criterion in Step III is given to finally determine the switching frequency against the parameter variations. The proposed SFSC method is also validated by the experiments.